MENGANYAM WARISAN LELUHUR: PEMBELAJARAN BATIK ANAK-ANAK DI TANJUNG BUMI SEBAGAI MODEL ETNOPEDAGOGI KREATIF - Regina, Belinda Dewi; Slamet Haryono; Udi Utomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The focus of this study is how the process of learning to make batik for children in Kampung Batik Tanjung Bumi not only functions as a skill inheritance, but also as a means of preserving local cultural values. The main problem raised is the low interest of the younger generation in traditional cultural heritage, especially Madurese batik, amidst the currents of modernization and globalization. This study aims to formulate a creative ethnopedagogy learning model based on local wisdom through batik activities, so that it can increase children's interest while maintaining the sustainability of tradition. The methodology used is a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with batik artisans, children participating in the learning, parents, and local traditional figures, as well as documentation of activities. Data analysis was carried out thematically by mapping interaction patterns, transmitted values, and creative innovations in learning. The results of the study show that learning to make batik in Tanjung Bumi is able to integrate ethical values, aesthetics, hard work, and respect for nature and ancestors. Children not only learn batik techniques, but also understand the philosophy of motifs, local history, and symbolic meanings contained in each motif. The formulated creative ethnopedagogy model emphasizes a participatory approach, educational games, and expressive space for motif innovation. Thus, batik learning for children becomes an effective means for the regeneration of craftsmen as well as the preservation of cultural heritage.